Phenolic resin-based hard carbon negative electrode material, preparation method and application thereof, and sodium ion battery
Through the preparation method of phenolic resin-based hard carbon materials, the problem of low performance of existing resin-based hard carbon materials in sodium ion batteries has been solved, and performance improvements such as conductivity and reversible capacity have been achieved.
Patent Information
- Application Number
- CN202510264940.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-18
AI Technical Summary
The performance of existing resin-based hard carbon materials in sodium ion batteries is not high, such as conductivity, first-time Coulomb efficiency, compaction density and cycle stability, which limits their application.
Phenolic resin is used as the substrate to prepare hard carbon negative electrode materials through steps such as raw material preparation, dehydration, curing, pre-carbonization, ball milling and calcining, and optimize process parameters to improve material performance.
The comprehensive performance of phenolic resin-based hard carbon anode material in sodium ion batteries has been significantly improved, including conductivity, reversible capacity, first-time Coulomb efficiency, compaction density and cycle stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy battery technology, and in particular to a phenolic resin-based hard carbon negative electrode material, a preparation method and application thereof, and a sodium ion battery. Background Art
[0002] In the secondary battery energy storage system, lithium ions have outstanding characteristics such as high energy density, long life, no memory effect, and low self-discharge rate. They have become an important energy source to meet people's growing demand for energy storage systems. The rapid development of lithium batteries has brought many conveniences to people's lives. For example, various portable electronic products, communication equipment, electric vehicles, etc. are inseparable from the application of lithium-ion batteries.
[0003] However, the unlimited consumption of limited lithium metal resources has also caused people to worry about the future development of batteries. Due to the limited and uneven distribution of lithium reserves, the cost of lithium-ion batteries has risen sharply. In addition, lithium-ion batteries have great safety risks, so it is urgent to find a cheap and safe alternative energy source.
[0004] Metallic sodium and lithium are elements of the same family, with similar charging and discharging properties and physical and chemical properties. On the other hand, the reserves of metallic sodium on Earth are far greater than lithium resources. Therefore, sodium-ion batteries can be used as an excellent alternative to lithium-ion batteries in our lives.
[0005] However, the radius of sodium ions is larger than that of lithium ions, and the intercalation compound formed by sodium and graphite is thermodynamically unstable, so graphite is not suitable for storing sodium ions, resulting in low specific capacity and poor stability of graphite, a negative electrode material for traditional commercial lithium-ion batteries, in sodium-ion batteries.
[0006] In comparison, hard carbon negative electrodes have higher specific capacity and stability in sodium ion batteries, so hard carbon materials have been widely studied in recent years. At present, there have been certain research results on the research of hard carbon negative electrode materials in sodium ion batteries, using some types of resins to prepare hard carbon negative electrode materials. However, when existing resin-based hard carbon materials are used to prepare sodium ion batteries, their overall performance such as conductivity, first coulomb efficiency, compaction density and cycle stability is still not high, which limits their application. Summary of the invention
[0007] In order to solve the deficiencies of the prior art mentioned in the above background technology, the present application provides a method for preparing a phenolic resin-based hard carbon negative electrode material, and its technical solution is as follows: The present application provides a method for preparing a phenolic resin-based hard carbon negative electrode material, which comprises the following steps: Raw material preparation and dehydration: the raw material components are mixed evenly to obtain a resin mixture, and then the resin mixture is dehydrated; Curing: Curing the dehydrated resin mixture at 105-115°C for 5.5-6.5h; Pre-carbonization: The cured resin mixture is crushed and then pre-carbonized at 800-900°C for 3.5-4.5h; Ball milling: ball mill the pre-carbonized and cooled resin mixture until the product particle size is 5 to 10 μm; Calcination: The ball milled product is calcined at 1600-1800℃ in a nitrogen atmosphere for 3-5h to obtain the product; wherein the nitrogen flow rate is 3-5LPM; The raw material components include high-performance phenolic resin and other ingredients; the other ingredients are one or more combinations of sodium hydroxide, graphite, polyacrylonitrile, ethylene glycol, and a curing agent.
[0008] In some embodiments, the preparation method comprises the following steps: Raw material preparation and dehydration: the raw material components are mixed and dispersed evenly with a homogenizer to obtain a resin mixture, and then the resin mixture is dehydrated for 0.66 to 1.34 hours; Curing: Pour the dehydrated resin mixture into the mold box, and then place it in an oven at 105-115°C for curing for 5.5-6.5h; Pre-carbonization: The cured resin mixture is crushed and then placed in a carbonization furnace for pre-carbonization at 800-900°C for 3.5-4.5 hours; Ball milling: The pre-carbonized and cooled resin mixture is ball milled in a ball mill until the product particle size is 5 to 10 μm; Calcination: Place the ball mill product in a rotary kiln and calcine it at 1600-1800°C for 3-5h to obtain the product.
[0009] In some embodiments, the high performance phenolic resin has a viscosity of 15000-20000 cp at 25° C., a free phenol content of ≤2.5% by mass, a free formaldehyde content of ≤0.5% by mass, and a solid content of ≥90%.
[0010] In some embodiments, the other ingredients are sodium hydroxide; the weight ratio of the high-performance phenolic resin to sodium hydroxide is 1000: (3-5).
[0011] In some embodiments, the other ingredients are a first ingredient and a second ingredient; the first ingredient is sodium hydroxide or a curing agent, and the second ingredient is graphite; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, and graphite is 1000: (3-5): (20-30); the weight ratio of the high-performance phenolic resin, graphite, and curing agent is 1000: (20-30): (2-5).
[0012] In some embodiments, the other ingredients are a first ingredient and a third ingredient; the first ingredient is sodium hydroxide or a curing agent, and the third ingredient is polyacrylonitrile; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, and polyacrylonitrile is 1000: (3-5): (6.5-9.5); the weight ratio of the high-performance phenolic resin, polyacrylonitrile, and curing agent is 1000: (6.5-9.5): (2-5).
[0013] In some embodiments, the other ingredients are sodium hydroxide, ethylene glycol and a curing agent; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, ethylene glycol and curing agent is 1000: (3-5.5): (18-22): (2-5). In some embodiments, the components of the curing agent include water, phosphoric acid, and p-toluenesulfonic acid; wherein the weight ratio of the water, phosphoric acid, and p-toluenesulfonic acid is (35-39): (35-39): (100±5).
[0014] In some embodiments, the curing agent consists of p-toluenesulfonic acid, phosphoric acid, and water.
[0015] In some embodiments, the particle size of the graphite is one or more combinations of 5 μm, 10 μm, and 20 μm.
[0016] In some embodiments, the ethylene glycol is EG200.
[0017] The present application also provides a phenolic resin-based hard carbon negative electrode material, which is prepared using the preparation method of the phenolic resin-based hard carbon negative electrode material as described above.
[0018] The present application also provides an application of a phenolic resin-based hard carbon negative electrode material in a sodium ion battery, wherein the hard carbon negative electrode is prepared by the preparation method of the phenolic resin-based hard carbon negative electrode material as described above.
[0019] The present application also provides a sodium ion battery, whose negative electrode material adopts the phenolic resin-based hard carbon negative electrode material as described above.
[0020] Based on the above, compared with the prior art, this application has the following beneficial effects: The phenolic resin-based hard carbon negative electrode material prepared by the present application scheme is used as a negative electrode material for sodium ion batteries in sodium ion batteries, and its comprehensive performance such as conductivity, reversible capacity, first coulombic efficiency, compaction density and cycle stability is improved. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0022] In the description of this application, it should be noted that all terms (including technical terms and scientific terms) used in this application have the same meanings as those generally understood by ordinary technicians in the field to which this application belongs, and cannot be understood as limitations on this application; it should be further understood that the terms used in this application should be understood to have meanings consistent with the meanings of these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this application.
[0023] In order to verify the effect of the present application scheme, the present application provides the following examples: Example 1 1. Weigh the raw material components: take 1000g of high-performance phenolic resin and 4g of sodium hydroxide.
[0024] 2. Preparation process: After mixing the raw material components, disperse them evenly with a homogenizer and then dehydrate for 1 hour; The dehydrated resin was poured into an aluminum box and then placed in an oven for curing at 110°C for 6 h; The solidified resin is first crushed, then put into the carbonization furnace for pre-carbonization at 850℃ for 4h, and then taken out after natural cooling; Use a ball mill to grind to a particle size of 5 to 10 μm; Finally, it was placed in a rotary kiln and calcined at 1700° C. for 4 hours, wherein the atmosphere of the rotary kiln was a nitrogen atmosphere with a nitrogen gas flow rate of 4 LPM.
[0025] 3. After testing, the phenolic resin-based sodium electric hard carbon material was obtained, with a specific surface area of 1.1063m 2 / g, compacted density 1.25 (g / cm 3 , 70MPa), conductivity 82.55 (BET.99.94MPa), reversible capacity 320 (mAh / g), first coulombic efficiency 88%, carbon yield 46%, 0.1C rate cycle 50 weeks, capacity retention rate 98.11%.
[0026] Example 2 The only difference from Example 1 is that the raw material components are weighed differently: 1000 g of high-performance phenolic resin, 4 g of sodium hydroxide, and 25 g of graphite; the preparation process is the same as that of Example 1; After testing, the phenolic resin-based sodium electric hard carbon material was obtained, with a specific surface area of 8.8580m 2 / g, compacted density 1.21 (g / cm 3 , 70MPa), conductivity 107.69 (BET.99.94MPa), reversible capacity 354 (mAh / g), first coulombic efficiency 90%, carbon yield 48%, 0.1C rate cycle 50 weeks, capacity retention rate 98.23%.
[0027] Example 3 The only difference from Example 1 is that the raw material components are weighed differently: 1000 g of high-performance phenolic resin, 25 g of graphite, and 2 g of curing agent; the preparation process is the same as that of Example 1; After testing, the phenolic resin-based sodium electric hard carbon material was obtained, with a specific surface area of 238.1857m 2 / g, compacted density 1.20 (g / cm 3 , 70MPa), conductivity 120.41 (BET.99.94MPa), reversible capacity 369 (mAh / g), first coulombic efficiency 92%, carbon yield 48%, 0.1C rate cycle 50 weeks, capacity retention rate 98.78%.
[0028] Example 4 The only difference from Example 1 is that the raw material components are weighed differently: 1000 g of high-performance phenolic resin, 4 g of sodium hydroxide, and 8 g of PAN. The preparation process is the same as that of Example 1; After testing, the obtained phenolic resin-based sodium electric hard carbon material has a specific surface area of 6.3711m 2 / g, compacted density 1.26 (g / cm 3 , 70MPa), conductivity 70.25 (BET.99.94MPa), reversible capacity 323 (mAh / g), first coulombic efficiency 86%, carbon yield 46%, 0.1C rate cycle 50 weeks, capacity retention rate 98.21%.
[0029] Example 5 The only difference from Example 1 is that the raw material components are weighed differently: 1000 g of high-performance phenolic resin, 4 g of sodium hydroxide, 8 g of PAN, and 2 g of curing agent; the preparation process is the same as that of Example 1; After testing, the obtained phenolic resin-based sodium electric hard carbon material has a specific surface area of 5.4389m 2 / g, compacted density 1.27 (g / cm 3, 70MPa), conductivity 60.94 (BET.99.94MPa), reversible capacity 321 (mAh / g), first coulombic efficiency 85%, carbon yield 46%, 0.1C rate cycle 50 weeks, capacity retention rate 98.09%.
[0030] Example 6 The only difference from Example 1 is that the raw material components are weighed differently: 1000 g of high-performance phenolic resin, 4 g of sodium hydroxide, 20 g of EG200, and 5 g of curing agent. The preparation process is the same as that of Example 1. The obtained phenolic resin-based sodium electric hard carbon material has a specific surface area of 241.3002m 2 / g, compacted density 1.22 (g / cm 3 , 70MPa), conductivity 118.42 (s / cm.99.94MPa), reversible capacity 356 (mAh / g), first coulombic efficiency 90%, carbon yield 48%, 0.1C rate cycle 50 weeks, capacity retention rate 98.44%.
[0031] The raw material types selected in the above embodiment are: The viscosity of the high-performance phenolic resin at 25°C is 18000cp, the mass content of free phenol is 2.2%, the mass content of free aldehyde is 0.4%, and the solid content is 91.6%. The components of the curing agent are composed of deionized water, phosphoric acid, and p-toluenesulfonic acid; wherein the weight ratio of water, phosphoric acid, and p-toluenesulfonic acid is 37:37:100. The graphite is a graphite product of Xiamen Kaina Graphene Technology Co., Ltd., and its particle size is 5μm; the ethylene glycol is EG200; the purity of p-toluenesulfonic acid is ≥99.9%.
[0032] The raw material component formula of the specific embodiment is summarized as shown in the following table: Table 1
[0033] The present application also provides the following comparative examples: Comparative Example 1 Existing sodium electric hard carbon negative electrode materials generally use biomass as a precursor for carbonization. The carbon yield of this type of technology is relatively low, generally around 30%-50%. At the same time, its electrochemical performance is lower than that of the resin-based sodium electric hard carbon negative electrode material of the embodiment of the present application.
[0034] Comparative Example 2 The difference between this comparative example and Example 3 is that the calcination temperature is 1000° C., and the other preparation processes and conditions are consistent with Example 3.
[0035] Comparative Example 3 The difference between this comparative example and Example 3 is that the pre-carbonization temperature is 700° C., and the other preparation processes and conditions are consistent with Example 3.
[0036] Comparative Example 4 The difference between this comparative example and Example 3 is that the calcination atmosphere is helium, and the other preparation processes and conditions are consistent with Example 3.
[0037] Comparative Example 5 The difference between this comparative example and Example 3 is that the curing temperature is 110°C, the curing time is 4 hours, and the other preparation processes and conditions are consistent with Example 3.
[0038] Comparative Example 6 The difference between this comparative example and Example 3 is that the viscosity of the high-performance phenolic resin is 12000 cp (the viscosity of the high-performance phenolic resin is not within the range of 15000 to 20000 cp), and the other preparation processes and conditions are consistent with those of Example 3.
[0039] The performance of the products obtained in the examples and comparative examples was tested, and the test results are shown in the following table: Table 2
[0040] Table 3
[0041] The test methods used in the specific embodiments and comparative examples are as follows: The carbon yield is the mass of the material after pre-carbonization divided by the mass before pre-carbonization.
[0042] Conductivity test: Weigh 1g of hard carbon powder and evenly fill it in a circular mold with a diameter of 10mm. Start the hydraulic system to gradually apply pressure from 10-120MPa according to the preset pressure. Record the resistance and thickness after maintaining the pressure for 10 seconds. After pressurizing to 120MPa, release the pressure to 3MPa, and measure the rebound data after maintaining the pressure for 10 seconds.
[0043] First charge and discharge coulombic efficiency and cycle stability test: Preparation of sodium electric hard carbon negative electrode: first, sodium electric hard carbon powder and binder CMC are prepared into slurry in a mass ratio of 85:5, wherein the solvent is N-methylpyrrolidone, and then the prepared slurry is coated on a 9mm round copper foil and vacuum dried (80℃, 12h) to obtain a hard carbon negative electrode material disc. The hard carbon negative electrode material sheet uses metallic sodium as the counter electrode to assemble into button cells, all of which are assembled using CR2032 button half cells. Among them, the electrolyte used in the assembled battery is 1.0 M NaPF 6 -Diglyme. Test conditions: First charge and discharge coulomb efficiency at 50 mAh*g -1The test was carried out at a current density of 0.01 to 2 V; the cycle stability was 1 A g -1 The test was carried out under current density and voltage range of 0.01~2V.
[0044] Analysis of the above test results shows that: The phenolic resin-based hard carbon negative electrode material prepared by the embodiment of the present application is used as a negative electrode material for sodium ion batteries in sodium ion batteries, and the comprehensive performance such as conductivity, reversible capacity, first coulombic efficiency, compaction density and cycle stability is improved.
[0045] Compared with the embodiments of the present application, the existing sodium electric hard carbon negative electrode material in Comparative Example 1 generally uses a biomass-based precursor for carbonization. The carbon yield of this type of technology is relatively low, generally around 30%-50%, which is lower than the embodiments of the present application. At the same time, the electrochemical performance in Comparative Example 1 is lower than that of the resin-based sodium electric hard carbon negative electrode material in the embodiments of the present application.
[0046] Compared with the embodiments of the present application, the phenolic resin-based hard carbon negative electrode material prepared in Comparative Examples 2-6, when used as a negative electrode material for sodium ion batteries in sodium ion batteries, has relatively poor comprehensive performance such as conductivity, reversible capacity, first coulombic efficiency, compaction density and cycle stability.
[0047] Based on the above, this application has the following design concepts and beneficial effects: The key points of the design of this application are: the coordination of the raw material component formula and specific process parameters, especially the coordination of the raw material component formula with specific curing process parameters (curing temperature and time), calcination process parameters (atmosphere, atmosphere flow, calcination temperature and time), pre-carbonization process parameters (pre-carbonization temperature and time) and other process parameters, and the optimization of the raw material components with specific characteristic parameters (such as the specific selection of the viscosity of high-performance phenolic resin). The above-mentioned design points work together to achieve the effect of this application: The phenolic resin-based hard carbon negative electrode material prepared by the present application scheme is used as a negative electrode material for sodium ion batteries in sodium ion batteries, and its comprehensive performance such as conductivity, reversible capacity, first coulombic efficiency, compaction density and cycle stability is improved.
[0048] It should be noted that: In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values; The phenolic resin-based hard carbon negative electrode material prepared in the present application can be used as a negative electrode material for sodium ion batteries, but is not limited to being suitable for sodium ion batteries.
[0049] In the embodiments of the present application, the hard carbon negative electrode is applied to the CR2032 type button half-cell for performance testing, which is only used to reflect the effect of the hard carbon negative electrode material prepared in the present application in sodium ion batteries, and does not mean that the hard carbon negative electrode prepared in the present application is only suitable for this.
[0050] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a phenolic resin-based hard carbon negative electrode material, characterized in that: The following steps are involved: Raw material preparation and dehydration: the raw material components are mixed evenly to obtain a resin mixture, and then the resin mixture is dehydrated; Curing: Curing the dehydrated resin mixture at 105-115°C for 5.5-6.5h; Pre-carbonization: The cured resin mixture is crushed and then pre-carbonized at 800-900°C for 3.5-4.5h; Ball milling: ball mill the pre-carbonized and cooled resin mixture until the product particle size is 5 to 10 μm; Calcination: The ball milled product is calcined at 1600-1800℃ in a nitrogen atmosphere for 3-5h to obtain the product; wherein the nitrogen flow rate is 3-5LPM; The raw material components include high-performance phenolic resin and other ingredients; the other ingredients are one or more combinations of sodium hydroxide, graphite, polyacrylonitrile, ethylene glycol, and a curing agent.
2. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: Raw material preparation and dehydration: the raw material components are mixed and dispersed evenly with a homogenizer to obtain a resin mixture, and then the resin mixture is dehydrated for 0.66 to 1.34 hours; Curing: Pour the dehydrated resin mixture into the mold box, and then place it in an oven at 105-115°C for curing for 5.5-6.5h; Pre-carbonization: The cured resin mixture is crushed and then placed in a carbonization furnace for pre-carbonization at 800-900°C for 3.5-4.5 hours; Ball milling: The pre-carbonized and cooled resin mixture is ball milled in a ball mill until the product particle size is 5 to 10 μm; Calcination: Place the ball mill product in a rotary kiln and calcine it at 1600-1800°C for 3-5h to obtain the product.
3. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 1, characterized in that: The high-performance phenolic resin has a viscosity of 15000-20000 cp at 25° C., a free phenol content of ≤2.5% by mass, a free aldehyde content of ≤0.5% by mass, and a solid content of ≥90%.
4. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 1, characterized in that: The other ingredients are sodium hydroxide; the weight ratio of the high-performance phenolic resin to sodium hydroxide is 1000: (3-5); Or, the other ingredients are the first ingredient and the second ingredient; the first ingredient is sodium hydroxide or a curing agent, and the second ingredient is graphite; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, and graphite is 1000: (3-5): (20-30); the weight ratio of the high-performance phenolic resin, graphite, and curing agent is 1000: (20-30): (2-5); Or, the other ingredients are the first ingredient and the third ingredient; the first ingredient is sodium hydroxide or a curing agent, and the third ingredient is polyacrylonitrile; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, and polyacrylonitrile is 1000: (3-5): (6.5-9.5); the weight ratio of the high-performance phenolic resin, polyacrylonitrile, and curing agent is 1000: (6.5-9.5): (2-5); Or, the other ingredients are sodium hydroxide, ethylene glycol and curing agent; wherein the weight ratio of the high-performance phenolic resin, sodium hydroxide, ethylene glycol and curing agent is 1000: (3-5.5): (18-22): (2-5).
5. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 4, characterized in that: The components of the curing agent include water, phosphoric acid and p-toluenesulfonic acid; Wherein, the weight ratio of water, phosphoric acid and p-toluenesulfonic acid is (35-39): (35-39): (100±5).
6. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 5, characterized in that: The curing agent consists of p-toluenesulfonic acid, phosphoric acid and water.
7. The method for preparing a phenolic resin-based hard carbon negative electrode material according to claim 1, characterized in that: The particle size of the graphite is one or more combinations of 5 μm, 10 μm, and 20 μm; The ethylene glycol is EG200.
8. A phenolic resin-based hard carbon negative electrode material, characterized in that: The material is prepared by the method for preparing a phenolic resin-based hard carbon negative electrode material as described in any one of claims 1 to 7.
9. Application of phenolic resin-based hard carbon negative electrode material in sodium ion battery, characterized in that: The hard carbon negative electrode is prepared by the preparation method of the phenolic resin-based hard carbon negative electrode material according to any one of claims 1 to 7.
10. A sodium ion battery, characterized in that: The negative electrode material is the phenolic resin-based hard carbon negative electrode material as claimed in claim 8.
Citation Information
Cited By
Hard carbon negative electrode material and preparation method thereof, negative electrode and battery
CN121626963A